Tide gauge observations of the Indian ocean tsunami, December 26, 2004, in Buenos Aires coastal waters, Argentina - Dragani, Walter Cesar (2006)
Sea level oscillations at the Buenos Aires province coastal waters were detected as a response to the magnitude 9.3 earthquake centered off the west coast of northern Sumatra (3.307°N, 95.947°E) on December 26, 2004 at 00:59 UTC. The aim of the present work is to report the first description on sea level oscillations in the Buenos Aires continental shelf generated by oceanic seismic activity. Sea level records gathered at three tide gauge stations located at Santa Teresita (36° 32′S, 56° 40′W), Mar del Plata (38° 05′S, 57° 30′W) and Puerto Belgrano (38° 54′S, 62° 06′W) were filtered and analyzed. The first arrival was measured at Mar del Plata (December 27, 2004, 00:15 UTC). At Santa Teresita and Puerto Belgrano, the tsunami reached the coast 33 min and 4.5 h later than at Mar del Plata, respectively. Maximum wave heights observed were 0.27, 0.15 and 0.20 m at Santa Teresita, Mar del Plata and Puerto Belgrano stations, respectively, and wave periods were detected in the range from 20 to 120 min. Wave amplitudes presented a remarkable temporal variability in the period immediately following tsunami wave arrival. After the first arrivals, waves lasted during the first 40 and 54 h at Mar del Plata and Santa Teresita, respectively. Even though, atmospherically forced sea level oscillations (in the tsunami frequency band) are frequently observed at different tide stations at locations on the Buenos Aires province coast, the weather patterns between December 24 and 27, 2004 showed no evidences of either frontal passages or atmospheric gravity waves. Thus sea level perturbations recorded at Santa Teresita, Mar del Plata and Puerto Belgrano stations can certainly be linked to the Indian Ocean tsunami.